An examination of the current National Operating Committee on Standards for Athletic Equipment system and a new pneumatic ram method for evaluating American football helmet performance to reduce risk of concussion. (June 2017) - Hoshizaki, Thomas Blaine; Karton, Clara; Oeur, R. Anna; Kendall, Marshall; Dawson, Lauren; Post, Andrew
Brain injuries are prevalent in the sport of American football. Helmets have been used which effectively have reduced the incidence of traumatic brain injury, but have had a limited effect on concussion rates. In an effort to improve the protective capacity of American football helmets, a standard has been proposed by National Operating Committee on Standards for Athletic Equipment that may better represent helmet-to-helmet impacts common to football concussions. The purpose of this research was to examine the National Operating Committee on Standards for Athletic Equipment standard and a new impact method similar to the proposed National Operating Committee on Standards for Athletic Equipment standard to examine the information these methods provide on helmet performance. Five National Operating Committee on Standards for Athletic Equipment–certified American football helmets were impacted according to the National Operating Committee on Standards for Athletic Equipment standard test and a new method based on the proposed standard test. The results demonstrated that the National Operating Committee on Standards for Athletic Equipment test produced larger linear accelerations than the new method, which were a reflection of the stiffer compliance of the standard meant to replicate traumatic brain injury mechanisms of injury. When the helmets were impacted using a new helmet-to-helmet method, the results reflected significant risk of concussive injury but showed differences in rotational acceleration responses between different helmet models. This suggests that the new system is sensitive enough to detect the effect of different design changes on rotational acceleration, a metric more closely associated with risk of concussion. As only one helmet produced magnitudes of response lower than the National Operating Committee on Standards for Athletic Equipment pass/fail using the new system, and all helmets passed the National Operating Committee on Standards for Athletic Equipment standard, these results suggest that further development of helmet technologies must be undertaken to reduce this risk in the future. Finally, these results show that it would be prudent to use both standards together to address risk of injury from traumatic brain injury and concussion.